Projeto Ciclo Rankine: estudo de caso sobre redução de custos - PIROPO, Eduardo dos Santos (2017)
The society has the challenge of reconciling the growing increase consumption of products and services with the consequent increase of energy electric demand and increasingly stringent environmental requirements, aiming at a sustainability scenario. In this context, the Rankine cycle has been adopted as a solution to increase the efficiency of thermal plants with single or open cycle. This work talks about the concepts and the usual arrangements of thermoelectric with heat recovery boilers to production steam and power addition through steam turbine and generator. The installation and operating costs of some of the main equipment are analyzed by calculating the total cost of the life cycle, considering the different alternatives of assembly and the different specifications of the equipments (American Petroleum Institute and American National Standards Institute), addition to evaluating the reliability considering different installation and options of custormization. Energy auctions tend to have low MWh values, so these actions are fundamental to get the success of the business and contribute to the development of the country's energy sector.